The Effect of Workload, Work Environment, Work Stress and Responsibility on Nurses' Job Satisfaction at Business Engaged in Health Service Sector - Sundari*, Zelvy Emmelya; Djumarno, Djumarno; Rochbini, Didik J; Lo, Singmin Johanes (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
The purpose of this study is to determine the impact of workload on job satisfaction. The study population consisted of 212 nurses at businesses engaged in the health service sector. This research includes quantitative research using survey procedures. Collection of information by observation, interviews, and questionnaires. The sample consisted of 139 nurses. Data analysis used a simple linear regression method. The research results obtained show that workload has a negative effect on job satisfaction. The temporal demands dimension has the most substantial negative relationship with the operating procedures dimension. This indicates that the more nurses are required to work quickly, the less job satisfaction nurses will have in implementing procedures. There is an influence of the work environment on nurse job satisfaction. Keywords: Workload; Work Environment; Work Stress; Responsibility; Job Satisfaction